Organizational citizenship behaviour in different type of primary schools in Malaysia - Talebloo, Baharak; Basri, Ramli; Asimiran, Soaib; Hassan, Aminuddin (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
The purpose of this study is to determine differences between the levels of organizational citizenship behaviours dimensions based on type of schools. In this research organizational citizenship behaviour model by Organ (1988) with five dimensions of (altruism, courtesy, conscientiousness, sportsmanship and civic virtue) was chosen. In the current study 410 primary school teachers from 72 schools in six education districts in Selangor state, Malaysia based on stratified random sampling were selected. Data were collected based on survey method and were analyzed by using descriptive and One-way ANOVA test. Reliability and validity (content, construct, convergent, and discriminant) analysis was conducted to confirm that the instrument is valid and reliable. The findings illustrated that among the dimensions of organizational citizenship behaviour, there was significant difference found to exist only in civic virtue dimension based on National, National type Chinese and National type Tamil school. According to the results National schools’ teachers showed more civic virtue behavior than National type Chinese teachers in Malaysian primary schools. The result of this study suggest several implications for Ministry of Education, policy makers, headmasters and teachers for improvement of schools through encouraging voluntary behaviours of workers and increasing exchange relationships within schools.